Monthly pulse methylprednisolone infusions in patients with non-idiopathic pulmonary fibrosis interstitial lung diseases: a single-center retrospective analyses - Dean Kellogg; Jay Peters; Jesse Sherratt; Sebastian Ocrospoma Heraud; Fatima Dollar; Anoop M. Nambiar (Therapeutic Advances in Respiratory Disease)
Background: Non-idiopathic pulmonary fibrosis interstitial lung diseases (non-IPF ILDs) comprise a broad spectrum of pathologies with varying degrees of inflammation and fibrosis. Progressive fibrosing ILD is associated with significant mortality and limited treatment options. Standard regimens employ multimodal immunosuppression, most commonly prolonged courses of oral corticosteroids (OCS), that are associated with a high risk of adverse effects and limited proven efficacy. Objectives: This study investigates the safety, tolerability, and effectiveness of monthly intravenous pulse methylprednisolone (PMP) for the treatment of patients with progressive non-IPF ILD. Design: Retrospective single-center cohort study of patients at an academic tertiary referral center for ILD between October 2019 and September 2022. Methods: All non-IPF ILD patients who received intravenous PMP (1000 mg daily for three consecutive days/month) between October 2019 and September 2022 were included. The decision to treat was based on a multidisciplinary consensus diagnosis following ATS/ERS/JRS/ALAT guidelines and confirmed or at high risk for ILD progression. Treatment continuation was contingent upon pulmonary function test (PFT) improvement (assessed approximately every 3 months), tolerable adverse events, and shared decision making with patients. Effectiveness was measured by a change in forced vital capacity (FVC) and diffusion limit of carbon monoxide (DLCO), with improvement being defined as an absolute increase in either FVC >5% or DLCO >10% from baseline. Results: Thirty-three patients received PMP at our center. One patient died of an acute exacerbation of ILD. Of the 32 patients included for analysis, 17 (53%) exhibited improved lung function with PMP between PFTs, which was maintained for a median follow-up of 209 days. The regimen was generally well-tolerated, with the most common adverse effects being insomnia and restlessness on infusion days. Advanced disease, indicated by lower FVC, traction bronchiectasis, and oxygen dependence, predicted poor response. Conclusions: PMP may offer a safer, better-tolerated, and more effective treatment for progressive non-IPF ILD than prolonged OCS. Notably, a third of fibrotic hypersensitivity pneumonitis patients showed improved FVC after 3 months of PMP, defying expectations of steroid non-responsiveness. However, further well-designed controlled prospective clinical trials are needed to confirm our findings and establish long-term safety.